The Indication for Cervical Cerclage and Pregnancy Outcome in a Teritiary Hospital in South-South Nigeria: A Five Year Review - Allagoa, Dennis; Agbo, John (European Scientific Journal, ESJ, 2019)
Background: Cervical incompetence is a major cause of second trimester miscarriage. Recurrent pregnancy loss in the second trimester is associated with significant distress. However, there should be a justifiable indication before a cerclage is inserted. There is no documentation of the indication of cervical cerclage and pregnancy outcome in Yenagoa, southsouth Nigeria. Objectives: This paper focuses on documenting the indication and obstetric outcome following cervical cerclage insertion at the Federal Medical Center Yenagoa, Bayelsa State. Methodology: A 5 year retrospective study was carried out in women who had cervical cerclage for cervical incompetence in the Federal Medical Centre, Yenagoa. The study was conducted from the 1 st of January 2014 to 31st of December 2018. All the case files of patients who had cervical cerclage were retrieved and reviewed. Results: A total of 41 patients had cervical cerclage. The commonest indication for cervical cerclage insertion was history indicated cerclage 59.4%. This was followed by ultrasound indicated cerclage 28.1% and rescue cerclage accounting for 12.5%. All patients employed McDonald’s method of cervical cerclage. The position of the knot wasin 12 0’ clock position in 53.1% of the patients and in the 6 0’clock position for 46.9% of the patients. The success rate following insertion of cerclage was 79.3%. The mode of deliveries was vaginal in 90.6% of the patients and 9.4% had caesarean section. Conclusion: There may be concern about the diagnosis of cervical incompetence. However, findings from this study clearly showed that the application of cervical cerclage is associated with good obstetric outcome.